2012
DOI: 10.1002/chin.201217180
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: A Convenient Synthesis of Novel 2,8‐Disubstituted Pyrido[3,4‐b]pyrazines Possessing Biological Activity.

Abstract: A Convenient Synthesis of Novel 2,8-Disubstituted Pyrido[3,4-b]pyrazines Possessing Biological Activity. -Condensation of suitable diaminopyridines [cf. (III)] with α-ketoaldehyde derivatives results in a regioselective synthesis of pyrido[3,4-b]pyrazines (IV). The 8-bromo substituent is utilized for the introduction of a variety of N-substituents including, amino, anilines, amides, and ureas. -(ANTOINE, M.; GERLACH, M.; GUENTHER, E.; SCHUSTER, T.; CZECH, M.; SEIPELT, I.; MARCHAND*, P.; Synthesis 2012, 1, 69-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The possibility of choosing the substituents of the chain, always seeking a better interaction with biological targets, and possible modulation of the lipophilic character of new derivatives, make semicarbazone intermediates important for the design of drugs [22]. In this context, in continuation of the work of our research groups in the development of new antitumor agents [23][24][25][26][27][28][29][30], the present study aimed to synthesize arylsemicarbazone derivatives with the purpose of evaluating their anticancer activity and their inhibition of protein kinases. Although the synthesis of some of these compounds has already been described in the literature [22,[31][32][33], the study of anticancer activity is reported for the first time in this work.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of choosing the substituents of the chain, always seeking a better interaction with biological targets, and possible modulation of the lipophilic character of new derivatives, make semicarbazone intermediates important for the design of drugs [22]. In this context, in continuation of the work of our research groups in the development of new antitumor agents [23][24][25][26][27][28][29][30], the present study aimed to synthesize arylsemicarbazone derivatives with the purpose of evaluating their anticancer activity and their inhibition of protein kinases. Although the synthesis of some of these compounds has already been described in the literature [22,[31][32][33], the study of anticancer activity is reported for the first time in this work.…”
Section: Introductionmentioning
confidence: 99%